(untitled) - Rich, Phil (New York, NY, 1998)
A source of support and expert guidance through a difficult life passage. Like a wise and comforting companion, this unique journal can help you to understand and work through those feelings of anger, fear, confusion, remorse, grief, and hopelessness that come along with the breakup of a marriage. The evocative writing exercises throughout The Healing Journey Through Divorce will provide you with the calm psychological space you need to collect your thoughts, sort out and reflect upon your feelings, and regain your bearings so that you can get on with the business of forging a new life for yourself and your loved ones. You will find The Healing Journey Through Divorce a valuable travel companion on your path to a fulfilling life.
Keywords: Divorce,Diaries,Diaries; Psychological aspects,Therapeutic use,Authorship,Psychological aspects